2021
DOI: 10.1007/s13346-021-01078-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of FDM 3D printing process parameters to produce haemodialysis curcumin-loaded vascular grafts

Abstract: Abstract3D printing has provided a new prospective in the manufacturing of personalized medical implants, including fistulas for haemodialysis (HD). In the current study, an optimized fused modelling deposition (FDM) 3D printing method has been validated, for the first time, to obtain cylindrical shaped fistulas. Printing parameters were evaluated for the manufacturing of fistulas using blank and 0.25% curcumin-loaded filaments that were produced by hot melt extrusion (HME). Four different fistula types have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Basile et al was manufacture TPU based vascular grafts with grade 80A with 0.25% curcumin to give antimicrobial properties. With the use of the 3D printing approach, it may be feasible to quickly produce a customized transplant straight from the patient's veins and arteries while preventing infection and maturation problems 113 . The primary cause of death in the elderly is cardiovascular disease (CVDs) 114 .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basile et al was manufacture TPU based vascular grafts with grade 80A with 0.25% curcumin to give antimicrobial properties. With the use of the 3D printing approach, it may be feasible to quickly produce a customized transplant straight from the patient's veins and arteries while preventing infection and maturation problems 113 . The primary cause of death in the elderly is cardiovascular disease (CVDs) 114 .…”
Section: Applicationsmentioning
confidence: 99%
“…With the use of the 3D printing approach, it may be feasible to quickly produce a customized transplant straight from the patient's veins and arteries while preventing infection and maturation problems. 113 The primary cause of death in the elderly is cardiovascular disease (CVDs). 114 The replacement of the blocked or constricted arteries, which is now the ideal vascular transplant combined with autograft transplantation, is a frequent medical surgery for the treatment of CVDs.…”
Section: Medical Sectormentioning
confidence: 99%
“…Generally, the isocyanates form the hard polyurethane segments, and diols or polyols groups form the soft polyurethane segments, providing tunable physical and mechanical properties depending upon the chain length. Several studies have demonstrated the application of TPU as vascular grafts [12], bone fixation screws [13], and drug delivery vehicles [14]. However, TPU has not yet been thoroughly explored as a biomaterial candidate for peripheral nerve tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%